Genomic DNA extraction from seed leaves of Gossypium barbadense L. for radioinduced mutations studies - Álvarez, Félix (2008)
A fast, simple and reliable method for the extraction of DNA from Gossypium barbadense radioinduced mutants has been developed. This method is cetyltrimethylammonium bromide (cTAB) based, and it extracts DNA from seed leaves processed in a 1.5 mL tube with 0.7 mL of extraction buffer; is highly efficient to cotton tissue and much cheaper in terms of time, chemical use and labor input. The described protocol presents consistent yield and good quality of DNA for several molecular analyses (AFLP, SSR, etc.).